Food Intake and Food Security as Determinants of Stunting Children Under Five Years - Ayik Nikmatul laili; Al Munawir; Farida Wahyuningtiyas (Health Notions, 2018)
Stunting is a linier growth failure caused by chronic malnutrition or chronic infectious disease. Stunting became nutritional problem that need attention because it can influence quality of human resources. Factors associated with stunting, such as nutrition intake, household food security, and parenting. Three work area health centers in Jember such as Sumberjambe, Kasiyan, and Sumberbaru which has highest rate of stunting children under five years in 2006. The purpose of this research was to analyze the determinant of stunting children under five years. This research was analytical observational with case control design. This research was conducted in three work area health centers such as Sumberjambe, Kasiyan, and Sumberbaru in September to October 2017. The sample of this research was 71 case respondents and 71 control respondents. Sampling technique used cluster random sampling. Logistic regression statistic test with significant level p < 0.05 was used to analyze the data. The result of this research showed that nutrition intake and household food security could influence incidence of stunting children under five years (each p-value was 0.00). Conclusion of this research was there significant influence noted between nutrition intake and food security on incidence of stunting children under five years. Keywords: Stunting, Nutrition intake, and Food security